Molecular characterization and antimicrobial resistance profile of Clostridium perfringens type A isolates from humans, animals, fish and their environment. (October 2017) - Yadav, Jay Prakash; Das, Suresh Chandra; Dhaka, Pankaj; Vijay, Deepthi; Kumar, Manesh; Mukhopadhyay, Asish Kumar; Chowdhury, Goutam; Chauhan, Pranav; Singh, Rahul; Dhama, Kuldeep; Malik, Satya Veer Singh; Kumar, Ashok
Abstract: The study was aimed to characterize, and determine antibiogram of C. perfringens type A isolated from the feces of human and animal diarrhoeal cases, as well as healthy animals, meat of pigs and goats, gills and intestine of fish and samples from fish pond. A total of 460 samples, including human diarrhoeal cases (n = 130); diarrhoeal cases of pig (n = 52) and goat (n = 50); fecal samples from healthy pig (n = 50) and goat (n = 50); meat samples viz . pork meat (n = 52); goat meat (n = 50) and fish including their environmental sources (n = 26) were used for isolation and identification of C. perfringens type A. All the biochemically confirmed isolates were positive for species-specific 16S rRNA and cpa genes by PCR assays. Toxinotyping of C. perfringens type A isolates showed that overall prevalence of C. perfringens type A with only cpa + gene was 43.2%; with cpa + and cpb2 + genes was 45.4%; with cpa + and cpe + genes was 4.9%; however, with cpa +, cpb2 + and cpe + genes was 6.6%. Antimicrobial susceptibility testing revealed that 83.7% of isolates were resistant to three or more antibiotics. Highlights: First ever systematic study in India emphasizes isolation and molecular characterization of Clostridium perfringens type A ( cpa ) from humans, animals, fish and their environmental sources. A high prevalence from pig diarrhoeal cases indicate pig might be a major source of C. perfringens type A.